Utilizing Niosome Nanoparticles for the Combined Treatment of Curcumin and Cisplatin in Oral Cancer - Rezaei, Fatemeh; Fesharakinia, Tara; Balsini Gavanaroudi, Soheil; Rezaeianjam, Maryam; Khanlari Goodarzi, Mahyar; Abdollahi, Maasoume; Akaberi, Kiomars (Asian Pacific Journal of Cancer Biology, 2024)
Overview: Oral cancer remains a significant health challenge due to its aggressive nature and limited treatment options. This study investigates the use of niosome nanoparticles to deliver a combination of curcumin and cisplatin, a natural anti-inflammatory and anti-cancer agent and a widely used chemotherapeutic drug, respectively. Methods: Niosome nanoparticles were formulated and optimized for encapsulation efficiency and stability. The physicochemical properties of the nanoparticles were characterized, including particle size, zeta potential, and polydispersity index (PDI). In vitro cytotoxicity assays were conducted using oral cancer cell lines to evaluate the efficacy of the combined treatment. Results: The niosome formulations with a mean particle size of approximately 150 nm, a favorable zeta potential of 24.6 ± 3.2 mV, and a low PDI of 0.23 ± 0.05. The release profile showed a controlled and sustained release of both curcumin and cisplatin over 48 hours, with a cumulative release of 51% for curcumin and 48% for cisplatin. In vitro studies revealed that the combined treatment significantly reduced cell viability compared to individual treatments, with a synergistic effect observed at specific concentrations. Conclusion: The findings suggest that niosome nanoparticles can effectively deliver a combination of curcumin and cisplatin, enhancing the therapeutic potential against oral cancer. This innovative approach may pave the way for more effective treatment strategies, ultimately improving patient outcomes in oral cancer therapy